Schedule-dependent cytotoxicity of methotrexate and 5-fluorouracil in human colon and breast tumor cell lines. - C Benz; M Schoenberg; M Choti; E Cadman (The Journal of Clinical Investigation, 1980)
The effect of sequential methotrexate and 5-fluorouracil on the clonal growth of the human colon adenocarcinoma cell, HCT-8, and the hormone-dependent human breast carcinoma cell, 47-DN, was examined. In both cell lines, when 5-fluorouracil was given during the last 6 h of a 24 h methotrexate exposure period, there was marked synergistic inhibition of clonal growth. Shorter intervals or the reverse sequence of drugs were either additive or antagonistic. These results indicate the importance of the drug sequence and time interval between drug administration for optimal cytotoxicity in these human cell lines. This information suggests that the administration of methotrexate 18 h before 5-fluorouracil may have potential application in the design of clinical trials for these malignancies.